2020
DOI: 10.1038/s41593-020-00748-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic organization of the human brain in post-traumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) affects approximately 8% of the general population, with higher rates in extreme stress groups, including combat veterans or victims of sexual assault. Despite extensive study of the neurobiological correlates of PTSD, little is known about its molecular substrates. Here differential gene expression and network analyses of 4 prefrontal cortex (PFC) postmortem subregions of male and female PTSD subjects demonstrates extensive remodeling of the transcriptomic landscape. The d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
147
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 102 publications
21
147
2
4
Order By: Relevance
“…A key up-regulated gene identified in Girgenti et al, ELK1 , was significantly up-regulated in both cortical regions in the present study, and the somatostatin gene ( SST ) , identified as robustly down-regulated in several regions of the cortex in Girgenti et al, was in the top ten of all down-regulated transcripts in both dlPFC and dACC here. ADAMTS2 , the second highest upregulated DEG in the combined cortical sample, was the top up-regulated gene in the dACC and the third most up-regulated in the dlPFC in Girgenti et al, 2020 55 . Both studies further found enrichment of PTSD-associated DEGs related to interneurons and their molecular functions.…”
Section: Discussionmentioning
confidence: 93%
“…A key up-regulated gene identified in Girgenti et al, ELK1 , was significantly up-regulated in both cortical regions in the present study, and the somatostatin gene ( SST ) , identified as robustly down-regulated in several regions of the cortex in Girgenti et al, was in the top ten of all down-regulated transcripts in both dlPFC and dACC here. ADAMTS2 , the second highest upregulated DEG in the combined cortical sample, was the top up-regulated gene in the dACC and the third most up-regulated in the dlPFC in Girgenti et al, 2020 55 . Both studies further found enrichment of PTSD-associated DEGs related to interneurons and their molecular functions.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to ADHD/epilepsy, a recent study highlighted the involvement of ELFN1 in post-traumatic stress disorder (PTSD) pathophysiology. Girgenti et al (2021) performed the first transcriptome-wide analysis of gene expression changes in the postmortem brain of a large cohort of PTSD subjects. RNA-seq analysis of four prefrontal cortex subregions from 52 PTSD subjects and 46 control subjects revealed the downregulation of ELFN1 and GABA-related genes such as GAD2 (glutamate decarboxylase 2), SST, PNOC (prepronociceptin), and SLC32A1 (VGAT) in the dorsolateral prefrontal cortex (dlPFC) of PTSD patients.…”
Section: Elfn1 Gene and Neuropsychiatric Disordersmentioning
confidence: 99%
“…RNA-seq analysis of four prefrontal cortex subregions from 52 PTSD subjects and 46 control subjects revealed the downregulation of ELFN1 and GABA-related genes such as GAD2 (glutamate decarboxylase 2), SST, PNOC (prepronociceptin), and SLC32A1 (VGAT) in the dorsolateral prefrontal cortex (dlPFC) of PTSD patients. In a transcriptome-wide association study, they identified ELFN1 as a gene conferring significant genetic liability for PTSD (Girgenti et al, 2021).…”
Section: Elfn1 Gene and Neuropsychiatric Disordersmentioning
confidence: 99%
See 2 more Smart Citations